Impact of a new electronic handover system in surgery - Ryan, Siobhan; Conlon, Kevin; Tierney, Sean; Ridgway, Paul; O'Riordan, James (My University, 2011)
Changing patterns of workflow in the hospital setting have highlighted the need for improvements in effective and safe handover of patient details. Financial constraints mean that hospitals are under increasing pressure to maximise efficiency and reduce length of stay of patients in hospitals and to reduce overtime bills for junior doctors. The European Working Time Directive (EWTD) for junior doctors also requires hospitals to comply with the 48 hour working week. This means the introduction of a shift-based work practice for junior doctors and subsequently an increased number of handovers between surgical on-call teams.
PUBLISHED
Keywords: Surgery; workflow; International Development; International Integration